Research Analysis of Hypnosis Methods in Mathematics and Science Education: Case Studies from Various Countries - Ika Putra Viratama; Didik Efendi; Sulis Maryanti; Fajar Dwi Mukti (Tarbiyah : Jurnal Ilmiah Kependidikan, 2026)
Mathematics and science education often face challenges related to students’ difficulty in understanding abstract and complex concepts. Using the Systematic Literature Review (SLR) method, this study analyzes the application of hypnosis in learning based on 67 articles from the Scopus, Taylor & Francis, CrossRef, ProQuest, Wiley Online Library, and JSTOR databases. The results show that the majority of studies focused on higher education (24 studies), followed by high school (20 studies), middle school (13 studies), and elementary school (10 studies). Based on geographic distribution, Indonesia contributed the most with 15 studies, followed by Germany and Japan. The findings confirm that positive suggestion and relaxation techniques in hypnosis are proven effective in improving focus, alleviating academic anxiety, and enhancing students’ motivation to learn. In conclusion, hypnosis has great potential to serve as an innovative method for supporting more effective, holistic, and adaptive learning in mathematics and science across various educational levels.